The goal of maturity in Ephesians 4:13-16 - E. D. Mbennah (Acta Theologica)
In this article, I argue that, in Ephesians 4:1-16, the author underscores spiritual maturity as the bridge between the new identity of the Christian (Eph. 1-3) and the moral code of the Christian life commensurate with the new identity (Eph. 4:17-6:20).1 I interpret Ephesians 4:13 to obtain the meaning of maturity. I critique the most notable interpretations and views in relation to Ephesians 4:13, after which, by way of structural analysis of Ephesians 4:13, I delineate the meaning of maturity and determine that, from its essence, maturity is essential for the Christian. This article provides the modern church an alternative way to view the theme and structure of Ephesians and an interpretation of Ephesians 4:13-16. New Testament scholars as well as church leaders, decision-makers in church work, generally, and Christian education planners will find this article quite engaging.